Effect of visual impairment on physical and cognitive function in old age: findings of a population-based prospective cohort study in Germany - Hajek, André; Weyerer, Siegfried (Journal of the American Geriatrics Society, 2016)
Objectives To examine how visual impairment affects physical and cognitive function in old age. Design A longitudinal population-based prospective cohort study. Setting General practitioner offices at six study centers in Germany. They were observed every 1.5 years over four waves. Participants Individuals aged 77-101 at follow-up Wave 2 (N = 2,394). Measurements Physical and cognitive function were assessed using an adapted scale that had been previously developed, and visual impairment was rated on a Likert scale (none, mild, severe or profound). Results Adjusting for sociodemographic factors and comorbidity, linear fixed-effects regression showed that the onset of severe visual impairment was associated with a decline in physical function score in the total sample (β = −0.15, P = .01) and in women (β = −.15, P = .03). Moreover, the onset of severe visual impairment was associated with decline in cognitive function score in the total sample (β = −0.38, P < .001) and in women (β = −0.38, P < .001) and men (β = −0.37, P = .001). Conclusion Visual impairment affects physical and cognitive function in old age. Interventional strategies to postpone visual impairment may contribute to maintaining physical and cognitive function.
Gesehen am 22.05.2019